This Librarian’s Journey of Testing New Search Innovations: From Retrieval to Artificial Intelligence (AI) - Abram, Stephen (Access: An International Journal of Nepal Library Association, 2024)
This article is the author’s personal journey of almost 50 years in adapting to and influencing technology change in the field of libraries of all types. He shares his learning and perspectives on the journey and how we often look at new technologies through the lenses of the past. We then mature through playing with and experiencing the new innovations and seeing the opportunities more clearly. His goal is to use the historical lens to inform our discussions and adoptions of current and future technologies such as the range of artificial intelligence applications that are emerging at rapid speed. He includes a glossary of the major technological adaptations and adoptions in libraries from an historical view and the current opportunities in AI, LLMs, agents, and more.